2021
DOI: 10.1016/j.neuroimage.2021.118609
|View full text |Cite
|
Sign up to set email alerts
|

Cross-dataset reproducibility of human retinotopic maps

Abstract: Population receptive field (pRF) models fit to fMRI data are used to non-invasively measure retinotopic maps in human visual cortex, and these maps are a fundamental component of visual neuroscience experiments. Here, we examined the reproducibility of retinotopic maps across two datasets: a newly acquired retinotopy dataset from New York University (NYU) ( n = 44) and a public dataset from the Human Connectome Project (HCP) ( n = 181). Our goal was to assess the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
114
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(128 citation statements)
references
References 96 publications
14
114
0
Order By: Relevance
“…It has been long debated whether V1 further distorts the visual field representation, or if V1 samples uniformly from RGCs, as reviewed previously [71,72]. Our analysis showed more cortical surface area devoted to the fovea than the parafovea and to the horizontal than vertical meridian, supporting previous findings using retinotopy informed by anatomy [101] and functional MRI [78,102,103,111]. Importantly, these eccentricity and polar angle non-uniformities are larger in V1 than they are in mRGC density, in agreement with findings from monkey [61,[73][74][75]112,113].…”
Section: Early Visual Cortex Does Not Sample the Retina Uniformlysupporting
confidence: 86%
“…It has been long debated whether V1 further distorts the visual field representation, or if V1 samples uniformly from RGCs, as reviewed previously [71,72]. Our analysis showed more cortical surface area devoted to the fovea than the parafovea and to the horizontal than vertical meridian, supporting previous findings using retinotopy informed by anatomy [101] and functional MRI [78,102,103,111]. Importantly, these eccentricity and polar angle non-uniformities are larger in V1 than they are in mRGC density, in agreement with findings from monkey [61,[73][74][75]112,113].…”
Section: Early Visual Cortex Does Not Sample the Retina Uniformlysupporting
confidence: 86%
“…It has been long debated whether V1 further distorts the visual field representation, or if V1 samples uniformly from RGCs, as reviewed previously [71,72]. Our analysis showed more cortical surface area devoted to the fovea than the parafovea and to the horizontal than vertical meridian, supporting previous findings using retinotopy informed by anatomy [101] and functional MRI [78,102,103,111]. Importantly, these eccentricity and polar angle nonuniformities are larger in V1 than they are in mRGC density, in agreement with findings from monkey [61, 73-75, 112, 113].…”
Section: Early Visual Cortex Does Not Sample the Retina Uniformlysupporting
confidence: 86%
“…However, a computational observer model has shown that these retinal asymmetries only account for a small proportion of behavioral contrast sensitivity asymmetries ( Kupers et al., 2019 , 2022 ). These asymmetries also exist and are greatly amplified, in the distribution of cortical surface area in the primary visual cortex, where there is substantially less surface dedicated to processing the upper vertical meridian than the lower vertical meridian ( Benson et al., 2021 ; Himmelberg et al., 2021a , b ). Thus, there is a reduction in neural resources allocated to the upper vertical meridian that could likely explain poorer visual performance.…”
Section: Discussionmentioning
confidence: 99%